Peranan Wanita Buruh Serabutan Dalam Menunjang Perekonomian Keluarga Di Desa Lunjen Kecematan Buntu Batu Kabupaten EnrekangIra - Indra Setiawan,; Nurhidayat Muh. Said,; St. Aisyah BM, (Jurnal Berita Sosial, 2024)
This research aims to: (1) To describe the economic conditions of the families of women who work as casual laborers in Lunjen Village, (2) To describe the efforts made by women who work as casual laborers to support the family economy in Lunjen Village. The type of research in this research is included in field research by explaining and describing conditions and phenomena more clearly regarding the situation that occurs, so the type of research used is descriptive-qualitative. Where the descriptive method is a method that attempts to describe a symptom, event or incident that is happening now. The data collection techniques used in this research are in-depth interviews, direct observation, and documentation to state the authenticity of the data, using data analysis in the form of data reduction, data presentation, and drawing conclusions. The results of the research show that: (1) The economic conditions of the families of women casual laborers in Lunjen Village can be categorized as prosperous families. This can be seen from (a) Part of the family income of female casual laborers can be saved, (b) The families of female casual laborers have assets in the form of gold, gardens and livestock, (c) All family members can eat meat, fish or eggs at least once a week, (d) All family members have different clothes for home and for traveling, (e) The house of the woman who works at casual jobs is categorized as a habitable house. (2) Apart from being a casual laborer to support the family economy. They also carry out other activities to support the family's economy by: (a) Making woven ropes that have sales value, (b) Selling various snacks and drinks, (c) Growing vegetables and fruit for sale, (d) Keeping livestock as an investment. The theoretical implication that can be conveyed in the context of this research regarding female workers is that it can be said that female workers have left the socio-cultural construction that has existed so far. Female workers have also proven that apart from their roles and responsibilities in the domestic realm as housewives, they can also play a role in the public realm to help their husbands in improving the family economy. Meanwhile, the practical implications of this research are the emancipation of female workers in helping to improve the family economy. By working as female workers in the public sector, we can break the assumption that only husbands or only men are worthy of working outside the home as breadwinners. Now female workers have also proven that they are also capable of working to earn a living for their families.